2021
DOI: 10.17223/19988621/73/9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Dimension of a Mathematical Model of Internal Ballistics on Design Parameters of a Shot for Grain Gunpowder Charges

Abstract: The problem of the impact of the mathematical model dimension on the calculated intraballistic characteristics of a shot for the charges made of granulated powder is considered. Mathematical models of the shot are studied using the spatial (axisymmetric), one-dimensional, and zero-dimensional (thermodynamic) formulations. The thermodynamic model takes into account the distribution of the pressure and velocity of a gas-powder mixture behind the shot for a channel of variable cross-section. Comparison of simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The calculations showed that the upper estimate of the decrease in the muzzle velocity of the projectile due to viscous friction is less than 0.5 %, the increase in the maximum pressure on the bottom of the channel is 1.5 % and the decrease in the maximum pressure on the bottom of the projectile is 1.1 %. The estimates made in [27] showed that one-dimensional and two-dimensional gas-dynamic models of internal ballistics based on the Euler equations differ in muzzle velocity by 1.0 %, in maximum pressure on the channel bottom by 3.0%, and in maximum pressure on the bottom of the projectile by 2.4 %. The level of differences between the studied parameters due to viscosity is less than these values.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The calculations showed that the upper estimate of the decrease in the muzzle velocity of the projectile due to viscous friction is less than 0.5 %, the increase in the maximum pressure on the bottom of the channel is 1.5 % and the decrease in the maximum pressure on the bottom of the projectile is 1.1 %. The estimates made in [27] showed that one-dimensional and two-dimensional gas-dynamic models of internal ballistics based on the Euler equations differ in muzzle velocity by 1.0 %, in maximum pressure on the channel bottom by 3.0%, and in maximum pressure on the bottom of the projectile by 2.4 %. The level of differences between the studied parameters due to viscosity is less than these values.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that the particle material is incompressible and the gas parameters inside and outside the powder elements in each section are the same. The system of equations for the internal ballistics of an artillery shot, which describes the flow of a heterogeneous reacting mixture, taking into account intergranular interaction in an axisymmetric formulation based on the Euler equations, is described in the work of the authors [27]. In addition to this model, instead of the Euler equations for the carrier phase, we will consider In Fig.…”
Section: Mathematical Model Of the Shotmentioning
confidence: 99%
See 2 more Smart Citations